Principles of Collaborative Education Research With Stakeholders: Toward Requirements for a New Research and Development Infrastructure. (October 2020) - Penuel, William R.; Riedy, Robbin; Barber, Michael S.; Peurach, Donald J.; LeBouef, Whitney A.; Clark, Tiffany
A group of collaborative approaches to education research sits uneasily within the existing infrastructure for research and development in the United States. The researchers in this group hold themselves to account to ways of working with schools, families, and communities that are different from the ways envisioned by models for education research promoted in U.S. policies and endorsed by U.S. federal agencies. Those models, widely supported by funders, privilege the research priorities of individual investigators and regularly yield products and findings with little relevance to educational practice. In this article, we review four collaborative approaches: Community-based Design Research, Design-based Implementation Research, Improvement Science in Networked Improvement Communities, and the Strategic Education Research Partnership. Through a participatory process involving developers and advocates for these approaches, we identified a set of interconnected principles related to collaboration, problem solving, and research. Further, we reviewed evidence of these principles in projects belonging to these four approaches. We contend it is worth attempting to understand, build upon, and support enactments of these principles in research proposals and projects, because there is evidence these approaches can promote agency and equity in education. To do so would require the field to develop criteria for judging quality, which peers can use to evaluate individual studies or sets of research; new outcomes by which to measure progress; new venues for developing and giving accounts of research; and an appreciation for the value of developing and cultivating relationships with educators, families, and communities as an integral part of research.